Stigma as a barrier to suicide prevention efforts in Iran - Masoomi, Maryam; Hosseinikolbadi, Seyedehmahboobeh; Saeed, Fahimeh; Sharifi, Vandad; Jalali Nadoushan, Amir Hossein; Shoib, Sheikh (Frontiers in Public Health, 2023)
Suicide and suicide attempt affect a considerable part of the general population, and in spite of their prevalence, the stigma associated with suicide remains an unsolved problem surrounding this important public health problem, especially in lower-income countries such as Iran. Evidence shows that help-seeking from formal mental health services for suicidal people is low in countries like Iran. Previous studies on Iranian survivors of suicide attempts have shown that these people experience fear of stigma due to labels such as loss of faith in God, having forms of severe mental illnesses (“madness”), and being involved in unaccepted sexual relationships. The associated stigma prevents them from seeking appropriate health and social services. Although both self-stigma and public stigma contribute to an unwillingness to seek mental health care and suicide prevention efforts in Iran, public stigma may be of greater consequence, significantly impeding an individual’s likelihood of accessing care for their suicidal thoughts or attempts. In such circumstances, many people with suicidal thoughts miss out on social and formal support programs offered by social and healthcare providers. In this perspective article, focusing on the public stigma regarding suicide in Iranian society, we address the challenges and barriers to seeking suicide prevention efforts in Iran and discuss culturally appropriate strategies to improve the current situation.